Pyrolysis-GC/MS Reference Data for Polymeric and Refractory Materials to Evaluate C-PVC Indicator Specificity - Isabel Goßmann; Corinna Wirth; Barbara M. Scholz-Böttcher (PANGAEA, 2025)
This dataset presents pyrolysis-gas chromatography-mass spectrometry (Py-GC/MS) data used to evaluate the specificity of proposed indicator compounds for identifying polyvinyl chloride (C-PVC) in environmental micro- and nanoplastic (MNP) samples. Pure standards of synthetic polymers - including various chlorinated and non-chlorinated types - refractory materials such as soot and charcoal, and natural polymers including different cotton-derived samples were analyzed under controlled conditions. Each polymer and material was pre-treated when applicable (e.g., Fenton oxidation), and subjected to Py-GC/MS using standardized protocols including on-line thermochemolysis with tetramethylammonium hydroxide (TMAH). Internal standardization was performed using deuterated polystyrene (d8-PS). Generated pyrograms were used to compare the presence and intensity of target indicator ions, such as those from naphthalene and its alkylated derivatives, and evaluate potential interference across sample types. This reference dataset aims to support method development and interpretation in the thermal analysis of C-PVC in complex environmental matrices.